2005
DOI: 10.1111/j.1523-1755.2005.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of altered mineral metabolism: The Dialysis Outcomes and Practice Patterns Study

Abstract: This study expands our understanding of the relationship between altered mineral metabolism and outcomes and identifies several potential opportunities for improved practice in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
508
8
25

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 673 publications
(564 citation statements)
references
References 17 publications
23
508
8
25
Order By: Relevance
“…Block et al (8) reported that the lowest multivariable adjusted relative risk for death occurred for serum phosphorus of 4.0 to 5.0 mg/dl with an adjusted 10% relative increase for 5.0 to 5.5 mg/dl. In Dialysis Outcomes and Practice Patterns Study (DOPPS), a serum phosphorus of 4.5 to 5.0 mg/dl had the lowest multivariable adjusted relative risk for death, with a 12% relative increase for 5.0 to 5.5 mg/dl (29). These and other findings from a European dialysis population (30) suggest that current K/DOQI goals may be too permissive of hyperphosphatemia Ͼ5.0 mg/dl (8,29,30).…”
Section: Elusive Target: Ideal Serum Phosphorusmentioning
confidence: 77%
“…Block et al (8) reported that the lowest multivariable adjusted relative risk for death occurred for serum phosphorus of 4.0 to 5.0 mg/dl with an adjusted 10% relative increase for 5.0 to 5.5 mg/dl. In Dialysis Outcomes and Practice Patterns Study (DOPPS), a serum phosphorus of 4.5 to 5.0 mg/dl had the lowest multivariable adjusted relative risk for death, with a 12% relative increase for 5.0 to 5.5 mg/dl (29). These and other findings from a European dialysis population (30) suggest that current K/DOQI goals may be too permissive of hyperphosphatemia Ͼ5.0 mg/dl (8,29,30).…”
Section: Elusive Target: Ideal Serum Phosphorusmentioning
confidence: 77%
“…Thus, PTX rates in CKD are clearly affected by trends in the medical treatment (4A) [6,10,11]. Prevalent basic PTX rates and PTX incidence at follow-up/ 100 patients/year between 1996 and 2001 were approximated per country in the Dialysis Outcome and Practice Pattern study (DOPPS) as follows: France 14.3 %, 1.8; Germany 6 %, 1; Italy 5 %, 0.9; Japan 4.1 %, 0.6; Spain 5.7 %, 1.5; UK 9.2 %, 1.5; USA 4 %, 0.5 [12].…”
Section: Resultsmentioning
confidence: 99%
“…14 Young e cols., analisando os resultados do primeiro Dialysis Outcomes and Practice Patterns Study (DOPPS), encontraram uma elevação de 13% no risco de mortalidade geral para cada aumento de 1 mEq/L de Ca no dialisato. 15 Essa preocupação com a sobrecarga de Ca foi um dos pontos determinantes para a recomendação de uma concentração de 2,5 mEq/L de Ca no dialisato pelo K/DOQI para a maioria dos pacientes, exceto em situações específicas, quando este pode ser mais alto ou baixo. 1 Na prática clínica, o primeiro DOPPS mostrou que apenas 40% dos pacientes estavam em uso de uma Cad recomendada pelo K/ DOQI.…”
Section: Racionalunclassified
“…Na Europa e no Japão, apenas 24% e 20% estavam em uso de Cad de 2,5 mEq/L, respectivamente. 15 No mais recente guia para o tratamento dos distúrbios do metabolismo mineral e ósseo da DRC foi sugerido o uso de Cad de 2,5 ou 3,0 mEq/L. 3 Apesar das poucas evidências sobre a concentração ideal de Ca no dialisato, algumas considerações devem ser observadas.…”
Section: Racionalunclassified
See 1 more Smart Citation